Agricultural trade policy : completing the reform (Institute for International Economics WashingtonUS, 1998)
Points ways that multilateral, regional and unilateral paths could be coordinated to liberalize agricultural trade. Proposes a set of multilateral talks that would benefit from agricultural reform at all levels and would complete the job begun at the Uruguay Round.
Keywords: AGRICULTURAL TRADE